1994
DOI: 10.1007/bf03403535
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide Signals Activation of Tumor Necrosis Factor Biosynthesis Through the Ras/Raf-1/MEK/MAPK Pathway

Abstract: Background: Lipopolysaccharide (LPS) is known to activate macrophages, causing the release of toxic cytokines that may provoke inflammation and shock. One of the most important and best studied of these cytokines is tumor necrosis factor (TNF). Details of the signaling pathway leading to TNF biosynthesis remain unclear. The pathway is branched in the sense that TNF gene transcription and TNF mRNA translation are both strongly stimulated by LPS. Recent evidence has indicated that MAP kinase homologs become phos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
87
1
2

Year Published

2000
2000
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(94 citation statements)
references
References 62 publications
4
87
1
2
Order By: Relevance
“…A previous study reported that down-regulation of TLR 4 expression, using RNA interference techniques, decreased MAPKs activation, TNF-α and MIP-2 expression in RAW 264.7 cells stimulated with LPS [17]. However, there are conflicting reports concerning the physiological role of ERK1/2 in the TNF-α production [17,34,36,37]. For example, Means, et al reported that inhibition of ERK1/2 led to a decrease in the degree of TNF-α expression in murine alveolar macrophage cell line AMJ2C-8, not in the RAW264.7 cells [36].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…A previous study reported that down-regulation of TLR 4 expression, using RNA interference techniques, decreased MAPKs activation, TNF-α and MIP-2 expression in RAW 264.7 cells stimulated with LPS [17]. However, there are conflicting reports concerning the physiological role of ERK1/2 in the TNF-α production [17,34,36,37]. For example, Means, et al reported that inhibition of ERK1/2 led to a decrease in the degree of TNF-α expression in murine alveolar macrophage cell line AMJ2C-8, not in the RAW264.7 cells [36].…”
Section: Discussionmentioning
confidence: 93%
“…JNK and ERK1/2 regulated TNF-α and MIP-2 expression and JNK (SP600125) or ERK1/2 inhibitor (PD98059) reduced these cytokines expression [14,15,[33][34][35]. A previous study reported that down-regulation of TLR 4 expression, using RNA interference techniques, decreased MAPKs activation, TNF-α and MIP-2 expression in RAW 264.7 cells stimulated with LPS [17].…”
Section: Discussionmentioning
confidence: 96%
“…In mammalian cells, MAPKs included three major groups, ERK, JNK, and p38. They could be activated by many proinflammatory stimuli and played important roles in the inflammatory process [10][11][12]. It was reported that MAPKs were involved in TNF-α biosynthesis in LPSstimulated macrophages [10][11][12].…”
Section: Discussionmentioning
confidence: 99%
“…LPS stimulates macrophages to release inflammatory cytokines, such as IL-1 and TNF-α. The molecular mechanism for IL-1 production includes the activation of ERK, JNK and p38, and the release of ROS, which play key roles in the LPS-mediated signal transductions between extracellular membrane stimulation, cytoplasmic response, and gene activation [44,62,63]. LPS-mediated PI3K/Rac/ p38 pathways play a dominant role in the regulation of proIL-1/IL-1; other pathways such as PKC/MEK/ERK and PI3K/Rac/JNK are less important [44].…”
Section: Discussionmentioning
confidence: 99%